The Study of Noise Suppression in a Multispectral Imaging System Based on CMOS Image Sensors - Shao, Ziheng (International Journal of Computer Science and Information Technology, 2024)
This paper focuses on noise suppression in a multispectral imaging joystick system based on CMOS image sensors. CMOS image sensors offer advantages such as low power consumption, high integration, and cost-effectiveness in multispectral imaging systems; however, noise remains a major bottleneck affecting imaging quality. This study provides a detailed analysis of the sources and characteristics of thermal noise, shot noise, and reset noise, and proposes corresponding noise suppression algorithms, including cooling techniques, mean filtering algorithms, and wavelet transform algorithms. Based on experimental design and parameter settings, the effectiveness and processing speed of each algorithm were evaluated. The results demonstrate that optimized noise suppression algorithms significantly improve the signal-to-noise ratio and image quality. Finally, this paper summarizes the research findings and anticipates future research directions, including algorithm optimization.